Zygogramma Bicolorata: A Natural Biocontrol Agent Against Parthenium hysterophorus - Shivam Satyawan Madrewar; Srishty, Apurva; Harshal Ramesh Bagul; Shubham Maroti Narwade; Rani, Nikita; Nimisha Ravindra Khadkikar (MultiTech Publisher, 2024)
Parthenium hysterophorus (Congress grass) is a significant weed problem in Indian agriculture, causing economic and ecological harm. This study evaluates the use of Zygogramma bicolorata (Mexican beetle) as a biological control method. Field trials were conducted over two years in Maharashtra, with beetles introduced to treatment plots and compared to control plots without beetles. Results showed an 80% reduction in Parthenium density, increased biodiversity (Shannon Index from 1.2 to 2.1), and a 12% boost in adjacent crop yields. Minimal impact on non-target species was observed. Farmers positively received this method for its ease and effectiveness. This study supports Zygogramma bicolorata as a sustainable, eco-friendly alternative to chemical herbicides for weed management.